Acceptance of Sexual Interest in Minors in Self-Referred Individuals Under Treatment – An Exploratory Pilot Study - Lampalzer, Ute; Tozdan, Safiye; von Franqué, Fritjof; Briken, Peer (Frontiers in Psychology, 2021)
Some therapists/scientists argue that “acceptance” of sexual interest in minors (SIM), i.e. the integration of the sexual preference into the individual self-concept, is a prerequisite for dealing with SIM in a responsible way. However, if one assumes that – even in some persons – SIM might change over time, “acceptance” could also run counter to therapeutic targets because the motivation to change as well as the specific self-efficacy for modifying SIM might be reduced. This exploratory pilot study analyzes the relationship between acceptance of SIM and 1) dynamic risk for contact sexual reoffending, 2) SIM and frequency of the use of child/adolescent (sexual abuse) imagery, 3) frequency of sexual desire/behavior towards children/adolescents, and 4) the change of the level of acceptance of SIM during the course of treatment. The majority of the participants (N = 79) was not exclusively interested in children (85 %) and used child pornography but did not commit child sexual abuse (54 %). Acceptance of SIM, frequency of the use of child/adolescent (sexual abuse) imagery and frequency of sexual desire/behavior towards children/adolescents are assessed via self-report questionnaires, dynamic risk for contact sexual reoffending is measured by STABLE-2007. Pretreatment data are analyzed via Spearman’s correlation (N = 79). Intragroup analysis compares acceptance of SIM from pre- and posttreatment (n = 35). There was no correlation between acceptance of SIM and dynamic risk for contact sexual reoffending. However, there was a medium, positive correlation between acceptance of SIM and the frequency of the use of legal imagery of children, a positive correlation between the item “My inclination is an integral part of my personality” and the frequency of the use of legal child sexual abuse imagery, and a positive correlation between acceptance of SIM and the frequency of sexual activities with minors. Acceptance of SIM did not change during the course of treatment. The results suggest that “acceptance” of SIM has to be discussed in a differentiated way, i.e. as possibly being associated with positive and negative outcomes as well.